State, Law and Religion in Pluralistic Societies: Austrian and Indonesian Perspectives ; Austrian-Indonesian Dialogue Symposium, 27-29 May, 2009, Vienna - Hafner, Astrid (Vandenhoeck Ruprecht, 2010)
This volume presents experiences and best-practice examples in managing religious diversity from a legal, political and local perspec tive. It marks an interesting point for the on-going discussion on integration and participation of Muslims in Europe and shows the need for ex - changing knowledge and experience in this field especially to fulfill the challenges in a globalized world. This book combines contributions from the Austrian-Indonesian Dialogue Symposium State, Law and Religion in Pluralistic Societies Austrian and Indonesian Perspectives, held in May 2009 in Vienna, organized by the Austrian and the Indonesian Ministry for Foreign Affairs in co-operation with the Faculty of Law. This symposium marked an important step to strengthen the dialogue between the countries on the level of civil service, universities and religious communities.